Investigating the effect of andrographolide on HMGCR protein expression in MDA-MB-231 - Abdulateef, Al-Hakam Ahmed (2019)
Breast cancer is the uncontrolled malignant cellular growth in the tissues of the breast. It is the second most prevalent type of cancer among women in terms of mortality rates and incidents with annual approximation of diagnosed cases exceeds 1.5 million. Triple-Negative Breast Cancer is a subtype of breast cancer that does not express any of the three receptors PR, ER and HER2 and comprises 15% of all breast cancer cases. Andrographis paniculata a plant originally found in Malaysia, India and many Southeast Asia countries, and traditionally used by locals to treat diseases like fever, dysentery, diabetes, obesity and malaria. Its major bioactive compound is called Andrographolide. Andrographolide has anti-cancer effect on various types of cancer. On breast cancer, studies have proven that it has anti-proliferative anti-metastatic effects on cancerous cells but has no effect on normal breast cell lines. 3-Hydroxy-MethylGlutaryl Coenzyme-A (HMGCR) is an enzyme (glycoprotein) has a significant role in the process of cholesterol biosynthesis of cholesterol through the mevalonate pathway. Western Blotting was used to analyze the HMGCR protein expression levels in MDA-MB-231 cells after treatment with 100mM of Andrographolide in time-dependent manner (4hrs, 24hrs and 48hrs). Inhibition of cellular proliferation and down regulation of HMGCR protein expression was observed in cells treated with 100mM of Andrographolide in time- dependent manner (4hrs, 24hrs and 48hrs) when compared with cells treated with only DMSO. Andrographolide exhibited anticancer effect on Triple-Negative Breast Cancer cell line (MDA-MB-231). It also had an influence on HMGCR protein expression.